ANALISIS PENGARUH PANDEMI COVID-19 TERHADAP ARUS KAS PERUSAHAAN INDUSTRI FARMASI (Studi Kasus PT. KALBE FARMA Tbk.) - Atmojo, Muhammad Dimas Try (Jurnal Kompetitif Bisnis, 2020)
Abstract Corona Virus Desease 2019 (Covid-19) is a virus that was present in 2020 and caused many impacts both health impacts and economic instability of the State. Even because the economy of the country is unstable many industries are affected and many companies are terminated or closed because of their inability to survive the crisis. Topic raised in this discussion is the impact of the COVID-19 pandemic on the cash flow of a company engaged in the pharmaceutical industry. The method used in this research is descriptive by linking the company's cash flow statement data with the current phenomenon with the example of PT. Kalbe Farma Tbk. The results of this study indicate that the cash flow of pharmaceutical industry companies is affected by the COVID-19 pandemic. However, the influence that can be obtained especially on cash flow is a positive effect because of an increase in cash flow compared to the previous year due to the increased demand for drugs, multivitamins, and supplements, so sales rose rapidly in the first quarter of 2020. Keywords: COVID-19 Pandemic, Company Cash Flow